Castles, pyramids and palaces - Young, Caroline; King, Colin; Page, Steve; Pringle, Mike. (Tulsa, OK : EDC Pub., 1989)
Describes the tools and materials used in building from early times to the present in all parts of the world. This book traces the fascinating story of building, from the first prehistoric huts to the skyscrapers of today. Do you know how the Pyramids, the Parthenon or the Taj Mahal were built? Who worked on them? What tools and building materials they used? This book answers these questions and many more. It tells you exactly how some of the most amazing buildings in the world were constructed. Colin King's illustrations are packed with detail and humor. They combine with concise text to make this book an excellent introduction to the world of building and architecture.
Story of building -- First buildings -- Pyramid builders -- Ancient Greeks -- Romans -- Fortress castles -- Cathedrals and churches -- Mayas, Aztecs, and Incas -- China and Japan -- Amazing castles -- Powerful cities -- Building with wood -- Mosques and minarets -- Buildings of the East -- Kings and palaces -- Russia -- Curves and columns -- North American builders -- Metal and glass -- Modern buildings -- Unusual buildings -- Time line -- Glossary -- Index.
"First published in 1989 by Usborne Publishing Ltd...London"--P. 48.
Includes index.
Keywords: Building -- History -- Juvenile literature; Architecture -- History -- Juvenile literature; Historic buildings -- Juvenile literature